2018
DOI: 10.1101/444109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A redox-regulated type III metacaspase controls cell death in a marine diatom

Abstract: Programmed cell death (PCD) in marine phytoplankton was suggested as one of the mechanisms that facilitates large scale bloom demise. Yet, the molecular basis for algal PCD machinery is rudimentary. Metacaspases are considered ancestral proteases that regulate cell death, but their activity and role in algae are still elusive. Here we biochemically characterized a recombinant metacaspase 5 from the model diatom Phaeodactylum tricornutum (PtMC5), revealing calcium-dependent protease activity. This activity incl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…In particular, the metacaspase TeMC of Trichodesmium was recently studied where it was found that the activity of metacaspase TeMC was significantly positively correlated with that of the caspase-like in the laboratory and field samples of Trichodesmium that underwent the apoptosis-like death [98]. This biochemical and physiological evidence directly linked the expression and activity of metacaspase with the occurrence of an apoptosis-like event in cyanobacterium, and this is similar to the PCD scenario in the marine diatom Phaeodactylum tricornutum [91] in which the PCD-associated role of metacaspase has been demonstrated by the overexpression and knockout experiment. Therefore, like the metacaspase in eukaryotic algae, cyanobacterial metacaspase might also play an important role in regulating PCD.…”
Section: The Mechanisms Of Programmed Death In Microcystismentioning
confidence: 64%
See 1 more Smart Citation
“…In particular, the metacaspase TeMC of Trichodesmium was recently studied where it was found that the activity of metacaspase TeMC was significantly positively correlated with that of the caspase-like in the laboratory and field samples of Trichodesmium that underwent the apoptosis-like death [98]. This biochemical and physiological evidence directly linked the expression and activity of metacaspase with the occurrence of an apoptosis-like event in cyanobacterium, and this is similar to the PCD scenario in the marine diatom Phaeodactylum tricornutum [91] in which the PCD-associated role of metacaspase has been demonstrated by the overexpression and knockout experiment. Therefore, like the metacaspase in eukaryotic algae, cyanobacterial metacaspase might also play an important role in regulating PCD.…”
Section: The Mechanisms Of Programmed Death In Microcystismentioning
confidence: 64%
“…However, extensive laboratory and field studies brought in an intricate scenario that metacaspases have multifaceted functions involved in either PCD-associated or non-PCD-associated activity [86]. Evidence to support the PCD-associated roles are derived from a series of experiments in the higher plant (Arabidopsis) [89], yeast (Saccharomyces cerevisiae) [90], and eukaryotic algae (marine diatom Phaeodactylum tricornutum) [91], as well as the bacterium Xanthomonas (γ-proteobacteria) [92]. As shown, inactivation or inhibition of the metacaspase in these organisms can significantly reduce or completely abrogate the occurrence of the apoptosis-like events.…”
Section: The Mechanisms Of Programmed Death In Microcystismentioning
confidence: 99%
“…It was suggested that ROS oxidize these cysteines, inducing disulfide bond formation, thereby increasing PtMC5 activity. This PTM leads to the execution of an RCD pathway [108]. Hence, this mechanism could be a link between ROS accumulation during the RCD induction phase and protease activation to start the execution phase [109].…”
Section: Plant Rcdmentioning
confidence: 99%
“…Further, metacaspases-5 from the model diatom Phaeodactylum tricornutum (PtMC5) possess calcium-dependent protease activity. This activity included auto-processing and cleavage after arginine residue (Van Creveld et al, 2018). Such type III metacaspase also controls cell death in a marine diatom.…”
Section: Distribution and Functional Specification Of Parasite Metacamentioning
confidence: 99%